TU2.6 Pre-Operative Optimisation of Elective IBD Patients: Are we meeting the standard?. (9th August 2022) - Allan, Jennifer; Craig, Sarah; Wallace, William
Abstract: Aim: Inflammatory bowel disease represents a significant healthcare burden. Management requires a multi-disciplinary approach and a combination of both surgical and medical considerations. The aim of this study was to compare current practice within our colorectal unit for pre-operative optimisation of IBD patients with ACPGBI recommendations, with the view of introducing a proforma for these patients to ensure pre-operative optimisation standards are met. Methods: This was a retrospective study identifying patients undergoing elective surgery for IBD in our unit between January 2019-October 2020. Data was collected on pre-operative management and compared to the broad principles of optimisation outlined by ACPGBI in their 2018 guidelines. Clavien-Dindo classification was used to define post-operative complications. Results: 94 patients were identified, 67 in 2019 and 27 patients in 2020. 4.3% had active intra-abdominal sepsis. No patients had a clearly documented comprehensive nutritional assessment. 15.6% patients were on oral steroids pre-operatively (Dose ≤30mg). 43.8% were on biologic therapy. Mean length of stay was 11.3days. 39.7% of patients experienced post-operative complications. However, only 12.8% of patients had a Clavien-Dindo score of ≥3. There was no mortality. Conclusion: ACPGBI guidelines highlight key areas for adequate pre-operative optimisation. Our study highlighted that our morbidity following IBD surgery was comparable to those in literature. However, key areas of improvement were identified including comprehensive nutritional assessment. Current work involves creating a pre-operative proforma to encompass this and will be followed by a re-audit.